The rheological properties of clay-water systems based on locally mined kaolin - Gerischer, F. R. G.(Friedrich Rudolf Gunther) (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD) -- University of Stellenbosch, 1980.